2020
DOI: 10.1038/s41598-020-70512-1
|View full text |Cite
|
Sign up to set email alerts
|

Permalloy nanowires/graphene oxide composite with enhanced conductive properties

Abstract: carbon-metal-based composites arise as advanced materials in the frontiers with nanotechnology, since the properties inherent to each component are multiplexed into a new material with potential applications. in this work, a novel composite consisting of randomly oriented permalloy nanowires (py nWs) intercalated among the sheets of multi-layered graphene oxide (Go) was performed. py nWs were synthesized by electrodeposition inside mesoporous alumina templates, while Go sheets were separated by means of sonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 58 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…The unique combination of high magnetic permeability, low coercivity, and excellent thermal stability makes permalloy an ideal candidate for various technological advancements, including magnetic sensors, magnetic random-access memory (MRAM), and spintronic devices [ 2 , 3 ]. In recent years, the exploration of permalloy at the nanoscale has gained prominence, with a particular focus on the synthesis, characterization, and manipulation of permalloy nanowires [ 4 , 5 ]. These nanoscale structures exhibit intriguing magnetic behaviors and offer great potential for further advancements in nanoelectronics and magnetic nanodevices.…”
Section: Introductionmentioning
confidence: 99%
“…The unique combination of high magnetic permeability, low coercivity, and excellent thermal stability makes permalloy an ideal candidate for various technological advancements, including magnetic sensors, magnetic random-access memory (MRAM), and spintronic devices [ 2 , 3 ]. In recent years, the exploration of permalloy at the nanoscale has gained prominence, with a particular focus on the synthesis, characterization, and manipulation of permalloy nanowires [ 4 , 5 ]. These nanoscale structures exhibit intriguing magnetic behaviors and offer great potential for further advancements in nanoelectronics and magnetic nanodevices.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 At the metal-carbon interface, d(metal)-π(carbon) orbital coupling can change the density of states, and spin population, and perhaps influence adsorption of MB. Jaimes et al 22 recently showed that permalloy, an alloy of 80% Ni and 20% Fe, in the form of nanowires integrated with graphene greatly improved the conductivity. For these reasons, a Ni-Fe alloy, near the permalloy composition, was selected as the metal material.…”
mentioning
confidence: 99%